The performance effect of early versus late carbohydrate feedings during prolonged exercise - Heesch, M. W. S.; Mieras, M. E.; Slivka, D. R. (Applied Physiology, Nutrition, and Metabolism, 2014)
The purpose of this study was to determine how the timing of isoenergetic carbohydrate feedings during prolonged cycling affects performance in a subsequent 10-km cycling time trial. Recreationally trained male cyclists (n = 8; age, 34.5 ± 8.3 years; mass, 80.0 ± 6.3 kg; body fat, 16.0% ± 3.8%, peak oxygen uptake, 4.54 ± 0.42 L/min) completed 4 experimental trials consisting of cycling continuously for 2 h at 62.4% ± 1.9% of peak oxygen uptake, followed immediately by a self-paced 10-km time trial. The 4 conditions included no carbohydrate ingestion (PP), early carbohydrate ingestion (CP), late carbohydrate ingestion (PC), or carbohydrate ingestion throughout (CC). Blood samples were obtained at 0, 60, and 120 min of cycling as well as at the conclusion of the time trial. The 10-km time trial time to completion was faster in trials CC (17.70 ± 0.52 min) and PC (17.60 ± 0.62 min) as compared with trial PP (18.13 ± 0.52 min, p = 0.028 and p = 0.007, respectively) while trial CP (17.85 ± 0.58 min, p = 0.178) was not. Serum glucose increased with carbohydrate feedings (p < 0.05), while serum free fatty acid concentrations were lower in trials PC and CC than trials CP and PP (p < 0.05). There was no difference in oxygen uptake, heart rate, rating of perceived exertion, or substrate use between trials (p > 0.05). These data indicate that carbohydrate ingestion throughout or late during a 2-h cycling bout can improve subsequent 10-km time trial performance.